Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/corr.0000000000001389
|View full text |Cite
|
Sign up to set email alerts
|

What Are Risk Factors for Infection after Primary or Revision Total Joint Arthroplasty in Patients Older Than 80 Years?

Abstract: Background Patients older than 80 years of age form an increasing proportion of the patient population undergoing total joint arthroplasty (TJA). With increasing life expectancy and the success of TJA, orthopaedic surgeons are more likely to operate on patients older than 80 years than ever before. Given that most other studies focus on younger populations, only evaluate primary TJA, or limit patient populations to institutional or regional data, we felt a large-database, nationwide analysis of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
10
1
Order By: Relevance
“…66 The notion that underlying confounders may skew the data in PearlDiver toward demonstrating a positive association between CSI and infection is partially supported by the finding that PearlDiver-derived analyses regarding the timing of CSI prior to arthroscopic shoulder surgery and TKA, for example, are also among the only studies to identify a link between CSI and subsequent postoperative infection in these fields. 37,[39][40][41][42]44,45,67,68 There are other limitations to the current systematic review and meta-analysis. Because much of the data included in the current study was from large registry databases, it is difficult to perform sub-group analyses to identify risk factors and drivers that may modulate the risk of infection following CSI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…66 The notion that underlying confounders may skew the data in PearlDiver toward demonstrating a positive association between CSI and infection is partially supported by the finding that PearlDiver-derived analyses regarding the timing of CSI prior to arthroscopic shoulder surgery and TKA, for example, are also among the only studies to identify a link between CSI and subsequent postoperative infection in these fields. 37,[39][40][41][42]44,45,67,68 There are other limitations to the current systematic review and meta-analysis. Because much of the data included in the current study was from large registry databases, it is difficult to perform sub-group analyses to identify risk factors and drivers that may modulate the risk of infection following CSI.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, preoperative CSIs have been identified as a risk factor for postoperative infection in a wide variety of orthopaedic procedures, from shoulder and hip arthroscopy, to total shoulder and total joint arthroplasty (TJA). [33][34][35][36][37][38][39][40][41][42][43][44][45] Based on these findings, it is commonplace in the field of TJA, for example, to delay operative treatment for 3 months following intraarticular CSI. 42,46 Even in the field of TJA, however, where these practices are largely standard-of-care, the growing number of studies, systematic reviews, and meta-analyses refuting this association have caused some to take pause and reassess the validity of this commonly held practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our purpose was to review the current evidence on the clinical implications of obesity, malnutrition, hypoalbuminemia, diabetes, anemia, smoking, and opioid use [52,68,79] in TJA and to propose evidence-based recommendations for the optimization of these risk factors. We found that they were associated with worse outcomes, including increased rates of in-hospital complications, transfusions, periprosthetic joint infections, revisions, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified modifiable risk factors in TJA that increase the risk of complications; these include deep and superficial infections, pulmonary emboli, and myocardial infarction [7,8]. Modifiable risk factors have also been associated with increased readmissions, length of stay, costs, and revisions [52,68,79]. Pruzansky et al [62] found that 80% of patients undergoing any TJA and 93% of patients undergoing revision TJA for periprosthetic joint infection had at least 1 modifiable risk factor, with the most common being morbid obesity (46%), anemia (29%), malnutrition (26%), and diabetes (20%).…”
Section: Introductionmentioning
confidence: 99%
“…a Abbreviations: BMI, body mass index; CHF, congestive heart failure; DVT, deep vein thrombosis; PE, pulmonary embolism. a p < 0.01. b p < 0.05.these conditions exist individually 12,14,16,17,19,21,[23][24][25]30,31. In contrast to the study hypothesis, morbid obesity was not associated with an increased risk of reoperation or component revision.…”
mentioning
confidence: 97%